A rare case of bevacizumab-related osteonecrosis of the jaw associated with dental implants - Gustavo Maluf; Rogério Jardim Caldas; Eduardo Rodrigues Fregnani; Paulo Sérgio da Silva Santos (SpringerOpen, 2019)
Abstract Background Medication-related osteonecrosis of the jaw (MRONJ) is characterized by the development of bone necrosis in the jaws of patients receiving antiresorptive and/or antiangiogenic medications. No scientific reports have been published yet on bevacizumab-related osteonecrosis of the jaw (BeRONJ) when associated with dental implant placement and adjuvant ozone therapy. Case presentation A 54-year-old female patient with a history of metastatic breast cancer and bevacizumab use presented with a dental infection. Dental extraction followed immediately by dental implant placement was planned after suspension of the bevacizumab treatment. The patient presented with pain, drainage of purulent secretion, and bone exposure 5 weeks post-surgery. Complete healing was achieved at postoperative 7 months. Conclusions The combination of adjuvant ozone therapy and surgical debridement was effective for the treatment of MRONJ; however, the risk of MRONJ may persist after the suspension of bevacizumab for 28 days.